2012
DOI: 10.1353/jda.2012.0036
|View full text |Cite
|
Sign up to set email alerts
|

Application Of The Alternative Techniques To Estimate Demand For Money In Developing Countries

Abstract: In this paper, we applied alternative time series techniques and obtained similar summaries of demand for money relations for twelve developing countries. This indicates that adequate attention should be paid to the purpose of research and interpretation of results rather than to econometric techniques. We also find that income elasticities are close to unity for almost all of our sample countries and the interest rate elasticities are well determined and significant. Further, it is shown that demand for money… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
3
8
0
1
Order By: Relevance
“…This supports the findings of Kumar et al (2013). This is also in line with other studies that focus on developing countries such as Singh and Kumar (2012), Nachega (2001) and Barro et al (2016). By implication, money is mostly held for the purpose of medium of exchange in Nigeria.…”
Section: Empirical Analysissupporting
confidence: 93%
“…This supports the findings of Kumar et al (2013). This is also in line with other studies that focus on developing countries such as Singh and Kumar (2012), Nachega (2001) and Barro et al (2016). By implication, money is mostly held for the purpose of medium of exchange in Nigeria.…”
Section: Empirical Analysissupporting
confidence: 93%
“…He also found that inflation exerted a significant influence on money demand in four of the countries. Singh and Kumar (2012) using alternative time series techniques for 12 developing countries found for almost all the sample countries that, the interest elasticities were well determined and significant. Abdullah, Ali, and Matahir (2010) reexamined the demand for money in Singapore, Malaysia, Thailand, Indonesia, and the Philippines.…”
Section: Empirical Evidence From Developing Countriesmentioning
confidence: 94%
“…Identification and endogeneity tests are also mandatory in this method. A good exposition of the JML technique can be found in Holtedahl and Joutz (2004), Singh and Kumar (2009) and Kumar (2009). 7 The results from other options such as no intercept or trend, unrestricted intercept no trend, unrestricted intercept restricted trend and unrestricted intercept unrestricted trend gave implausible income elasticity.…”
Section: Cointegration and Granger Causalitymentioning
confidence: 99%